Exfoliative Cellular Study of Pathological Body Fluids – 1 year Retrospective Study - Kuntal Devesh Patel (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Body fluids are straightforwardly gained by tapping. For fluid routine and microscopicexamination, laboratory receives pleural, peritoneal, CSF, Urine and Synovial fluids. The cytologicalevaluation and biochemical study of these received fluids can be fruitful as assistance to the diagnosis.Present study is an attempt to analyze all the samples referred for cytological evaluation.Method: The study is cross-sectional descriptive, analytical and retrospective kind of study carried out inCentral Laboratory of Dhiraj Hospital, over a period of one year from June2019 to May2020. Fluids suchas peritoneal, pleural, CSF, synovial, etc. were received were examined under light microscope and foundpathologies are classified in malignant and non-malignant entities. A total of 506 body fluids were receivedin the one year period. Majority of the cases were Peritoneal fluid comprised of 242 (47.8 %) followed bypleural fluid with 162 cases (32.0 %). Majority cases were categorized under Non-malignant group. Slightmale dominance was observed with the mean age of 46.2 years.Conclusion: Thorough analysis and appropriate clinical correlation will aid in improving patient treatmentand care. Cytology of the fluid is a rapid and simple diagnostic technique for diagnosis of pathologicalconditions in malignant and non-malignant cases.